The interior design handbook - Ramstedt, Frida, ....-; Olofsson, Mia, ....-; Graves, Peter, 1942- (London : Particular Books, 2020)
When interior designer Frida Ramstedt moved from a characterful old apartment to a functional new build, she started to think about design in a new way. Rather than relying on high ceilings and architectural features, she had to make full use of essential principles to transform a blank canvas into a cosy, attractive and harmonious home. In doing so, she distilled the secrets of successful interior design and styling. This is a book about what looks good and why, filled with practical tips and illustrations to help you work out what's best for your space and lifestyle - and to discover what your individual tastes really are. With advice on everything from how to hang curtains to how to apply the golden ratio, The Interior Design Handbook is an indispensable guide for every home.
Keywords: Interieurvormgeving